EVALUASI HASIL RADIOGRAF CRANIUM PROYEKSI ANTERO POSTERIOR MENGGUNAKAN VARIASI KV DI INSTALASI RADIOLOGI RUMAH SAKIT HERMINA ARCAMANIK: THE EVALUATION OF CRANIUM RADIOGRAF USING ANTERO POSTERIOR PROJECTION WITH DIFFERENT kV AT RADIOLOGICAL DEPARTMENT OF HERMINA HOSPITAL IN ARCAMANIK - Nurrohman, Farhan; Ardiana; Nuramdiani, Dian (JURNAL TERAS KESEHATAN, 2024)
The provision of exposure factors is the key to producing quality radiographs in providing accurate anatomical information. This study aimed to determine the difference in anatomical information from radiographs of cranium examination as an indication of radiograph quality in the selection of several exposure factors. The study was conducted at Hermina Arcamanik Hospital in April 2024. A phantom cranium was used as the object, and the exposure factor was set at a variation of the tube voltage value 60-80kV with the tube current value fixed at 20mAs. The radiographs were evaluated for anatomical details and analyzed through the Friedman test. The results showed that the anatomical information for each tube voltage value was 4.18 for 60kV, 3.91 for 65kV, 3.50 for 70kV, 2.27 for 75kV, and 1.14 for 80kV. The value of 60kV/20mAs has the highest mean rank value indicating that this exposure factor provides the most optimal anatomical detail